The genus Potimirim in Central America (Crustacea, Atyidae) - Smalley, Alfred E. (1963)
Examination of males of Potimirim glabra show that P. brasiliana is the same species. P. americana is not closely related to the other known species. P. mexicana is found on the Atlantic slope of Costa Rica. The biology and distribution of P. glabra in Costa Rica is discussed.